Delivering Next-Generation Public Services through Mobile Technology - Nirupam Bajpai; Abhishek Beriya; John Biberman; Anchal Sharma; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
With the ongoing dramatic drop in prices for smartphones in India and the broader developing world, new frontiers are opening up for the incorporation of mobile technology into public service delivery. Mobile services in the fields of education and health have already been widely disseminated, with enormous potential for future growth. Such platforms both improve the quality of the user experience and provide data which can vastly improve the public decision-making process. The expansion of public services into the realm of mobile technology will only be accelerated if governments synchronize the deployment of capable mobile platforms with investments in the digital infrastructure needed to support them. However, while this path presents great promise, it also risks deepening the digital divide. Implementing mobile-based public service delivery presents a number of roadblocks such as India's relatively low rate of smartphone ownership, broadband infrastructure limitations, and overcoming the legacy of pre-digital institutions. These will need to be addressed in order to facilitate a smooth and inclusive transition towards applying these powerful technologies, but a successful outcome would mean a profound transformation of the Indian economy.
Keywords: 330